Blast furnace tapping main channel castable based on microporous mullite-silicon carbide enhancement
By using microporous mullite-silicon carbide reinforcement in the blast furnace main groove castable, combined with boron carbide, modified graphite and modified silicon sol, the problem of insufficient fluidity and high temperature resistance of existing materials is solved. It achieves higher oxidation resistance and flexural strength, and extends service life.
Patent Information
- Application Number
- CN202411687234.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The fluidity and high temperature resistance of the castable material in the existing blast furnace outlet main groove need to be improved, resulting in the material being prone to cracking and peeling, and its service life is short.
Using a blast furnace iron-out main groove castable based on microporous mullite-silicon carbide reinforcement, the material's oxidation resistance, chemical corrosion resistance and flow resistance of high-temperature slag are improved by adding boron carbide, modified graphite and modified silicon sol. sex.
It significantly improves the oxidation resistance, high-temperature flexural strength and fluidity of the castable material, extends its service life, and enhances its resistance to high-temperature slag.
Smart Images

Figure BDA0005149911070000111 
Figure BDA0005149911070000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, in particular to a blast furnace tapping main groove castable based on microporous mullite-silicon carbide reinforcement. Background Art
[0002] The main iron ditch at the blast furnace taphole is a channel that guides high-temperature molten iron and molten slag. The function of the main iron ditch is to separate the molten iron from the slag. The slag in the ditch enters the slag discharge ditch from the top of the skimmer beam, and the molten iron flows through the molten iron channel at the bottom of the skimmer beam to achieve separation of iron and slag.
[0003] The iron ditch castable is a refractory material for the lining of the iron ditch. It is subjected to high-temperature erosion and chemical corrosion from molten iron and slag during use. At the same time, it is subjected to repeated alternation of hot and cold for a long time, and is prone to cracking and peeling. The main reasons for this phenomenon are the low strength and poor oxidation resistance of the material. Therefore, its performance directly determines the service life of the iron ditch, and then determines the production capacity and efficiency of the blast furnace. Therefore, the blast furnace iron ditch material is one of the key refractory materials affecting blast furnace production.
[0004] The blast furnace ironmaking process is accompanied by the formation of slag. The slag is an alkaline oxide that can easily react with the iron channel refractory material to form a liquid phase, which weakens the scouring resistance of the main iron channel material and makes the erosion more serious. In order to improve the slag erosion resistance of the refractory material for the iron channel, carbon materials and calcium aluminate cement are usually added to the main channel castable as a binder. Although carbon materials have high thermal conductivity and low thermal expansion coefficient, they have poor oxidation resistance and water does not wet the graphite surface, resulting in extremely poor dispersion of graphite in water, thus affecting the castable fluidity, an important construction performance. Castables with calcium aluminate cement as a binder will introduce a certain amount of CaO and form low-melting products during high-temperature use, affecting the service life of the castable material. In order to better improve the performance and life of Al2O3-SiC-C castables, their resistance to chemical erosion, oxidation resistance and fluidity of high-temperature slag need to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a blast furnace tapping main ditch castable based on microporous mullite-silicon carbide reinforcement, which is used to solve the technical problems in the prior art that the fluidity of the castable and the high temperature resistance of the cast product need to be improved.
[0007] The purpose of the present invention can be achieved by the following technical scheme: a blast furnace iron-tapping main ditch castable based on microporous mullite-silicon carbide reinforcement comprises the following components by weight: 50-54 parts of fused brown corundum, 3-5 parts of fused brown corundum powder, 4-6 parts of white corundum powder, 16-18 parts of silicon carbide, 6-8 parts of alumina powder, 0.2-0.6 parts of boron carbide, 1-3 parts of modified graphite, 2-3 parts of silicon dioxide powder, 1-3 parts of elemental silicon powder, 120-140 parts of modified silica sol and 0.2-0.5 parts of water reducer.
[0008] Furthermore, the blast furnace iron-outlet main ditch castable based on microporous mullite-silicon carbide reinforcement is characterized in that the particle size of fused brown corundum is 5-8mm, the particle size of fused brown corundum powder is 0.5-1mm, the particle size of white corundum powder is 0.001-0.044mm, the particle size of silicon carbide is 1-3mm, the particle size of alumina micropowder is 0.5-1μm, the particle size of boron carbide is 1-3mm, the particle size of modified graphite is 200 mesh, the silica micropowder is 200 mesh, the particle size of elemental silicon powder is 0.001-0.037mm, and the water reducer is polycarboxylate.
[0009] The reaction mechanism of boron carbide is:
[0010] As the amount of B4C fine powder added increases, more C is retained, and more β-SiC is generated during the reaction, and the correspondingly greater high-temperature flexural strength is generated. During the heat treatment process, boron-containing silicate glass phase is easily generated, and an anti-oxidation film is more easily formed on the surface. B4C can oxidize before C and Si, reducing the oxidation reaction of C and Si and playing a role in protecting C and Si, which increases the amount of β-SiC generated by the reaction at high temperature, so the high-temperature flexural strength of the material also increases accordingly.
[0011] Furthermore, the microporous mullite-silicon carbide reinforced blast furnace iron tapping main ditch castable is characterized in that the modified silica sol is processed by the following steps:
[0012] A1. Add silane coupling agent, ethanol solvent and deionized water into a magnetic stirrer and stir. Raise the stirring temperature of the magnetic stirrer to 50-60°C and keep the temperature for 1-2 hours to obtain a pre-supported body.
[0013] A2. Add the preform and silica sol into a grinding and dispersing mixer and stir. Add acetic acid solution to adjust the pH of the system to 5-6. Increase the temperature of the grinding and dispersing mixer to 50-60° C. and keep the temperature for 1-2 hours to obtain a modified silica sol.
[0014] The synthetic reaction mechanism of modified silica sol is:
[0015] During the heating process, as the water evaporates, the silica sol forms a Si-O-Si gel network structure and produces a gelled bond. As the temperature continues to rise, the adsorbed water and structural water in the silica sol are lost. After the water in the water-based colloid is removed, the remaining gel becomes a highly active binder framework, SiC is oxidized to form a SiO2 protective film, the volume density of the castable increases, and the apparent porosity decreases. The hydrolysis of the silane coupling agent promotes the condensation of the silica sol particles. After high-temperature treatment, it promotes the continuous generation of mullite, and has a large aspect ratio and a dense structure, which significantly improves the thermal shock resistance and volume stability of the castable.
[0016] Furthermore, the microporous mullite-silicon carbide reinforced blast furnace iron-outlet main ditch castable is characterized in that the silane coupling agent is methyltrimethoxysilane, the silane coupling agent, ethanol solvent, and deionized water are used in a ratio of 10-20g:60-100mL:20-60mL, and the speed of the magnetic stirrer is 650r / min; the silica sol is an alkaline silica sol binder, and its particle size is 10-20nm, pH=9.5, and density is 1.20g·cm -3 The speed of the grinding and dispersing mixer is 400r / min, the ratio of the preform and the silica sol is 9mL:10mL, and the concentration of the acetic acid solution is 0.1moL / L.
[0017] Furthermore, the microporous mullite-silicon carbide reinforced blast furnace iron-tapping main ditch castable is characterized in that the modified graphite is processed by the following steps:
[0018] B1. Wash the flake graphite with deionized water until it is neutral, put it into a vacuum drying oven and dry it to constant weight, and grind and screen the flake graphite to obtain pretreated flake graphite;
[0019] B2, pre-treated flake graphite, metallic silicon, silicon carbide powder, and organic polymer binder are mixed to form a mucus, and post-processed to obtain a modified flake graphite precursor;
[0020] B3. Add the modified flake graphite precursor and surfactant KS1055 into a reactor and stir. Set the stirring speed to 550-600 r / min. Age for 3-5 hours and post-treat to obtain modified graphite.
[0021] Furthermore, the blast furnace iron-outlet main ditch castable based on microporous mullite-silicon carbide reinforcement is characterized in that, in step B1, the flake graphite is 198 flake graphite with a particle size of 80-100 mesh, and the temperature of the vacuum drying oven is 100-110°C.
[0022] Furthermore, the microporous mullite-silicon carbide reinforced blast furnace iron-outlet main ditch castable is characterized in that, in step B2, the metallic silicon is 98 metallic silicon, the silicon carbide particle size is 2-5 μm, the polymer binder is one of epoxy resin and acrylic resin, the weight ratio of pre-treated flake graphite, metallic silicon, silicon carbide powder, and organic polymer binder is 12-14g:1-2g:1-2g:50-60mL, and the post-processing operation includes: placing the mixed mucus in a muffle furnace, raising the temperature of the muffle furnace to 500-800°C, heat preservation for 5-6h, cooling and discharging, crushing, and passing through a 100-mesh sieve to obtain a modified flake graphite precursor.
[0023] Furthermore, the microporous mullite-silicon carbide reinforced blast furnace iron-tapping main ditch castable is characterized in that, in step B3, the modified flake graphite precursor and the surfactant KS1055 are used in a ratio of 10-15g:50-60mL; the post-treatment method includes: after aging, suction filtration, washing the filter cake with purified water until it is neutral and then drying it, transferring the filter cake to a drying oven at a temperature of 80-90°C, vacuum drying to constant weight, crushing, and passing through a 100-mesh sieve to obtain modified graphite.
[0024] The synthesis mechanism of modified flake graphite precursor is:
[0025] When graphite is added with metallic silicon or silicon carbide powder, the graphite and other refractory materials are bonded to the surface of the core through the bonding force of the binder under the action of external force. As the core grows, it becomes a large particle with a certain density and strength. The amount of water added is significantly reduced, so the density is correspondingly improved, which improves the problems of low density and poor filling of graphite and has a higher oxidation temperature.
[0026] The synthesis mechanism of modified graphite is:
[0027] The change in the wettability of the solid surface is due to the adsorption of the surfactant at the solid-liquid interface, which causes its molecules to be neatly oriented on the solid surface to form an adsorption layer. For flake graphite, the surfactant molecules adsorbed on the lipophilic surface have their lipophilic groups facing the graphite surface and their water groups facing the aqueous solution, which converts the original lipophilic solid surface into a hydrophilic solid surface, reduces the contact angle between the liquid and the solid, and improves the wettability of the graphite in water.
[0028] The present invention has the following beneficial effects:
[0029] 1. The microporous mullite-silicon carbide reinforced blast furnace tapping main ditch castable of the present invention adds boron carbide to the castable, and boron oxide and boron-containing silicate glass phase are easily generated during the heat treatment process, which promotes sintering and easily forms an anti-oxidation film on the surface of the castable. B4C can be oxidized before C and Si, reducing the oxidation reaction of carbon and silicon, protecting carbon and silicon, thereby increasing the amount of β-SiC generated by the reaction at high temperature, so that the oxidation resistance, high temperature resistance and flexural strength of the castable are also increased accordingly.
[0030] 2. The microporous mullite-silicon carbide reinforced blast furnace iron-tapping main ditch castable of the present invention modifies the silica sol by adding a coupling agent, so that the silicic ether generated by the reaction of the coupling agent and the silicon dioxide particles has a strong lipophilicity on the surface of the silicon dioxide particles, thereby enhancing the compatibility of the silica sol with organic matter; at the same time, a flexible surface layer is provided for the silica sol, which will enable the stress between the surface layers of the silica sol to be evenly transmitted, thereby enhancing the strength and toughness of the silica sol material, and effectively preventing the cracking of the material. At the same time, the hydrolysis of the silane coupling agent promotes the condensation of the silica sol particles, and the mullite phase is continuously generated during the high-temperature treatment process. At the same time, the single silicon powder is completely reacted and converted into silicon carbide, silicon dioxide and mullite. In addition, silicon carbide and mullite whiskers are in-situ generated in the pores and gaps inside the original layer, thereby improving the thermal shock stability and high-temperature and room-temperature strength of the castable and thus extending its service life.
[0031] 3. The microporous mullite-silicon carbide reinforced blast furnace iron-outlet main ditch castable of the present invention is modified by adding metallic silicon, silicon carbide powder and surfactant to graphite. The spinel coating formed on the surface of the flake graphite has good compatibility with the oxide matrix, thereby improving the bonding condition between the castable aggregate and the matrix, so that the load-softening performance of the castable is also improved. At the same time, the presence of the surface coating also becomes a barrier to prevent oxygen diffusion, thereby improving the antioxidant performance of the castable. As the particle nucleus grows, it becomes a large particle with a certain density and strength, and the amount of water added is significantly reduced, so that the degree of compactness is correspondingly improved, thereby improving the problems of low density and poor filling of graphite, thereby improving the wettability of water to the modified graphite and improving the fluidity of the castable. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The surfactant in the present invention is selected from Shandong Poly Chemical Co., Ltd. with a commercial brand name of KS1055;
[0034] The epoxy resin is bisphenol A epoxy resin E-51;
[0035] The acrylic resin was selected from Foshan Shengchuangda Chemical Co., Ltd. and its commercial grade is B-692.
[0036] Example 1
[0037] The preparation method of the blast furnace iron tapping main ditch castable based on microporous mullite-silicon carbide reinforcement of the present embodiment comprises the following steps:
[0038] S1. Preparing a preform
[0039] Weigh: 100 g of methyltrimethoxysilane, 600 mL of ethanol solvent, and 200 mL of deionized water, add a magnetic stirrer and stir, raise the stirring temperature of the magnetic stirrer to 50 ° C, and keep the temperature for 1 hour, wherein the speed of the magnetic stirrer is 650 r / min; silica sol is an alkaline silica sol binder, and its particle size is 10 nm, pH = 9.5, and density is 1.20 g cm -3 , and obtain a preform.
[0040] S2. Preparation of modified silica sol
[0041] Weigh: 900 mL of preform and 1000 mL of silica sol, add them into a grinding and dispersing mixer for stirring, add acetic acid solution to adjust the pH of the system to 5, increase the temperature of the grinding and dispersing mixer to 50° C., and keep the temperature for reaction for 1 hour, wherein the speed of the grinding and dispersing mixer is 400 r / min to obtain modified silica sol.
[0042] S3. Preparation of pretreated flake graphite
[0043] The flake graphite is washed with deionized water until it is neutral, placed in a vacuum drying oven at a temperature of 100° C. and dried to a constant weight, and the flake graphite is ground and screened to obtain pretreated flake graphite.
[0044] S4. Preparation of modified flake graphite precursor
[0045] Weigh: 120g of treated flake graphite, 10g of metallic silicon, 10g of silicon carbide powder, and 500mL of organic polymer binder to form a mixed mucus, put the mixed mucus into a muffle furnace, increase the temperature of the muffle furnace to 500-800°C, keep it warm for 5-6h, cool it down, grind it, and pass it through a 200-mesh sieve to obtain a modified flake graphite precursor.
[0046] S5. Preparation of modified graphite
[0047] Weigh 100 g of modified flake graphite precursor and 500 mL of surfactant KS1055, add them into the reactor and stir, set the stirring speed to 550 r / min, age for 3 h, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 80°C, vacuum dry to constant weight, crush, and pass through a 200-mesh sieve to obtain modified graphite.
[0048] S6. Preparation of casting material
[0049] Weigh by weight: 50 parts of fused brown corundum with a particle size of 5-8mm, 3 parts of fused brown corundum powder with a particle size of 0.5-1mm, 4 parts of white corundum powder with a particle size of 0.001-0.044mm, 16 parts of silicon carbide with a particle size of 1-3mm, 6 parts of alumina powder with a particle size of 0.5-1mm, 0.2 parts of boron carbide with a particle size of 1-3mm, 1 part of modified graphite with a particle size of 200 mesh, 2 parts of silica powder with a particle size of 200 mesh, 1 part of elemental silicon powder with a particle size of 0.001-0.037mm, and 0.2 parts of polycarboxylate. Pour the mixture into a cement mortar mixer and stir. Add 120 parts of modified silica sol into the cement mortar mixer and mix well to obtain a castable.
[0050] Example 2
[0051] The preparation method of the blast furnace iron tapping main ditch castable based on microporous mullite-silicon carbide reinforcement of the present embodiment comprises the following steps:
[0052] S1. Preparing a preform
[0053] Weigh: 100 g of methyltrimethoxysilane, 600 mL of ethanol solvent, and 200 mL of deionized water, add a magnetic stirrer and stir, raise the stirring temperature of the magnetic stirrer to 50 ° C, and keep the temperature for 1 hour, wherein the speed of the magnetic stirrer is 650 r / min; silica sol is an alkaline silica sol binder, and its particle size is 10 nm, pH = 9.5, and density is 1.20 g cm -3 , and obtain a preform.
[0054] S2. Preparation of modified silica sol
[0055] Weigh: 900 mL of preform and 1000 mL of silica sol, add them into a grinding and dispersing mixer for stirring, add acetic acid solution to adjust the pH of the system to 5, increase the temperature of the grinding and dispersing mixer to 50° C., and keep the temperature for reaction for 1 hour, wherein the speed of the grinding and dispersing mixer is 400 r / min to obtain modified silica sol.
[0056] S3. Preparation of pretreated flake graphite
[0057] The flake graphite is washed with deionized water until it is neutral, placed in a vacuum drying oven at a temperature of 100° C. and dried to a constant weight, and the flake graphite is ground and screened to obtain pretreated flake graphite.
[0058] S4. Preparation of modified flake graphite precursor
[0059] Weigh: 120g of treated flake graphite, 10g of metallic silicon, 10g of silicon carbide powder, and 500mL of organic polymer binder to form a mixed mucus, put the mixed mucus into a muffle furnace, increase the temperature of the muffle furnace to 500-800°C, keep it warm for 5-6h, cool it down, grind it, and pass it through a 200-mesh sieve to obtain a modified flake graphite precursor.
[0060] S5. Preparation of modified graphite
[0061] Weigh 100 g of modified flake graphite precursor and 500 mL of surfactant KS1055, add them into the reactor and stir, set the stirring speed to 550 r / min, age for 3 h, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 80°C, vacuum dry to constant weight, crush, and pass through a 200-mesh sieve to obtain modified graphite.
[0062] S6. Preparation of casting material
[0063] Weigh by weight: 52 parts of fused brown corundum with a particle size of 5-8mm, 4 parts of fused brown corundum powder with a particle size of 0.5-1mm, 5 parts of white corundum powder with a particle size of 0.001-0.044mm, 17 parts of silicon carbide with a particle size of 1-3mm, 7 parts of alumina powder with a particle size of 0.5-1mm, 0.4 parts of boron carbide with a particle size of 1-3mm, 2 parts of modified graphite with a particle size of 200 mesh, 2 parts of silica powder with a particle size of 200 mesh, 2 parts of elemental silicon powder with a particle size of 0.001-0.037mm, and 0.3 parts of polycarboxylate. Pour the mixture into a cement mortar mixer and stir. Add 130 parts of modified silica sol into the cement mortar mixer and mix well to obtain a castable.
[0064] Example 3
[0065] The preparation method of the microporous mullite-silicon carbide reinforced blast furnace main ditch castable in this embodiment includes the following steps:
[0066] S1. Preparing a preform
[0067] Weigh: 100 g of methyltrimethoxysilane, 600 mL of ethanol solvent, and 200 mL of deionized water, add a magnetic stirrer and stir, raise the stirring temperature of the magnetic stirrer to 50 ° C, and keep the temperature for 1 hour, wherein the speed of the magnetic stirrer is 650 r / min; silica sol is an alkaline silica sol binder, and its particle size is 10 nm, pH = 9.5, and density is 1.20 g cm -3 , and obtain a preform.
[0068] S2. Preparation of modified silica sol
[0069] Weigh: 900 mL of preform and 1000 mL of silica sol, add them into a grinding and dispersing mixer for stirring, add acetic acid solution to adjust the pH of the system to 5, increase the temperature of the grinding and dispersing mixer to 50° C., and keep the temperature for reaction for 1 hour, wherein the speed of the grinding and dispersing mixer is 400 r / min to obtain modified silica sol.
[0070] S3. Preparation of pretreated flake graphite
[0071] The flake graphite is washed with deionized water until it is neutral, placed in a vacuum drying oven at a temperature of 100° C. and dried to a constant weight, and the flake graphite is ground and screened to obtain pretreated flake graphite.
[0072] S4. Preparation of modified flake graphite precursor
[0073] Weigh: 120g of treated flake graphite, 10g of metallic silicon, 10g of silicon carbide powder, and 500mL of organic polymer binder to form a mixed mucus, put the mixed mucus into a muffle furnace, increase the temperature of the muffle furnace to 500-800°C, keep it warm for 5-6h, cool it down, grind it, and pass it through a 200-mesh sieve to obtain a modified flake graphite precursor.
[0074] S5. Preparation of modified graphite
[0075] Weigh 100 g of modified flake graphite precursor and 500 mL of surfactant KS1055, add them into the reactor and stir, set the stirring speed to 550 r / min, age for 3 h, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 80°C, vacuum dry to constant weight, crush, and pass through a 200-mesh sieve to obtain modified graphite.
[0076] S6. Preparation of casting material
[0077] Weigh by weight: 54 parts of fused brown corundum with a particle size of 5-8mm, 5 parts of fused brown corundum powder with a particle size of 0.5-1mm, 6 parts of white corundum powder with a particle size of 0.001-0.044mm, 18 parts of silicon carbide with a particle size of 1-3mm, 8 parts of alumina powder with a particle size of 0.5-1mm, 0.6 parts of boron carbide with a particle size of 1-3mm, 3 parts of modified graphite with a particle size of 200 mesh, 3 parts of silica powder with a particle size of 200 mesh, 3 parts of elemental silicon powder with a particle size of 0.001-0.037mm, and 0.5 parts of polycarboxylate. Pour the mixture into a cement mortar mixer and stir. Add 140 parts of modified silica sol into the cement mortar mixer and mix well to obtain a castable.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 3 is that, in the microporous mullite-silicon carbide reinforced blast furnace tapping main ditch castable used, no silane coupling agent is added in step S1.
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 3 is that in the microporous mullite-silicon carbide reinforced blast furnace main ditch castable used, no surfactant is added in step S5.
[0082] Comparative Example 3
[0083] The difference between this comparative example and Example 3 is that in the microporous mullite-silicon carbide reinforced blast furnace main ditch castable used, no boron carbide is added in step S6.
[0084] Performance Test:
[0085] According to GB / T4513.4-2017 "Monomorphous Refractory Materials Part 4: Determination of Castable Fluidity", the flow value of the castable sample is determined;
[0086] The castable was poured into the mold for vibration molding, cured at room temperature for 24 hours, and demolded for 24 hours to obtain a microporous mullite-silicon carbide reinforced blast furnace iron-making main ditch castable product sample. According to GB / T4513.6-2017 "Unshaped Refractory Materials Part 6: Determination of Physical Properties", the linear change rate, flexural strength and compressive strength of the castable product sample after heat treatment at 1500°C were tested. The specific test results are shown in Table 1 below.
[0087] Table 1-Performance test data of the sample
[0088]
[0089]
[0090] Data Analysis:
[0091] Comparative analysis of the data in Table 1 above shows that the flow value of the main ditch castable for blast furnace iron-making based on microporous mullite-silicon carbide reinforcement of the present invention reaches 220 mm, and the castable sample after heat treatment at 1500 ° C has a cold flexural strength of 14.2 MPa, a compressive strength of 93.9 MPa, and a hot flexural strength of 4.8 MPa. The permanent line change rate of the main ditch castable for blast furnace iron-making based on microporous mullite-silicon carbide reinforcement reaches 0.2%; all performance test data are better than those of the comparative example, indicating that the present invention is to modify the silica sol by a sol-gel method, and to generate a composite material by adding boron carbide powder and modified graphite powder at high temperature, which can improve the poor hydrophilicity and difficult dispersion of graphite, and can also enhance the high temperature flexural strength and antioxidant and corrosion resistance of the castable, and extend its service life.
[0092] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A blast furnace tapping main ditch castable based on microporous mullite-silicon carbide reinforcement, characterized in that: The invention comprises the following components in parts by weight: 50-54 parts of fused brown corundum, 3-5 parts of fused brown corundum powder, 4-6 parts of white corundum powder, 16-18 parts of silicon carbide, 6-8 parts of alumina powder, 0.2-0.6 parts of boron carbide, 1-3 parts of modified graphite, 2-3 parts of silicon dioxide powder, 1-3 parts of elemental silicon powder, 120-140 parts of modified silica sol and 0.2-0.5 parts of water reducer.
2. The blast furnace iron-tapping main ditch castable based on microporous mullite-silicon carbide reinforcement according to claim 1, characterized in that: The particle size of fused brown corundum is 5-8mm, the particle size of fused brown corundum powder is 0.5-1mm, the particle size of white corundum powder is 0.001-0.044mm, the particle size of silicon carbide is 1-3mm, the particle size of alumina powder is 0.5-1μm, the particle size of boron carbide is 1-3mm, the particle size of modified graphite is 200 mesh, the silica powder is 200 mesh, the particle size of elemental silicon powder is 0.001-0.037mm, and the water reducer is polycarboxylate.
3. The microporous mullite-silicon carbide reinforced blast furnace main ditch castable according to claim 1, characterized in that: The modified silica sol is processed by the following steps: A1. Add silane coupling agent, ethanol solvent and deionized water into a magnetic stirrer and stir. Raise the stirring temperature of the magnetic stirrer to 50-60°C and keep the temperature for 1-2 hours to obtain a pre-supported body. A2. Add the preform and silica sol into a grinding and dispersing mixer and stir. Add acetic acid solution to adjust the pH of the system to 5-6. Increase the temperature of the grinding and dispersing mixer to 50-60° C. and keep the temperature for 1-2 hours to obtain a modified silica sol.
4. The microporous mullite-silicon carbide reinforced blast furnace main ditch castable according to claim 3, characterized in that: The silane coupling agent is methyltrimethoxysilane, the proportion of silane coupling agent, ethanol solvent and deionized water is 10-20g:60-100mL:20-60mL, and the speed of the magnetic stirrer is 650r / min; the silica sol is an alkaline silica sol binder, and its particle size is 10-20nm, pH=9.5, and density is 1.20g·cm -3 The speed of the grinding and dispersing mixer is 400r / min, the ratio of the preform and the silica sol is 9-10mL:10-11mL, and the concentration of the acetic acid solution is 0.1moL / L.
5. The microporous mullite-silicon carbide reinforced blast furnace main ditch castable according to claim 1, characterized in that: The modified graphite is obtained by processing the following steps: B1. Wash the flake graphite with deionized water until it is neutral, put it into a vacuum drying oven and dry it to constant weight, and grind and screen the flake graphite to obtain pretreated flake graphite; B2, pre-treated flake graphite, metallic silicon, silicon carbide powder, and organic polymer binder are mixed to form a mucus, and post-processed to obtain a modified flake graphite precursor; B3. Add the modified flake graphite precursor and surfactant KS1055 into a reactor and stir. Set the stirring speed to 550-600 r / min. Age for 3-5 hours and post-treat to obtain modified graphite.
6. The microporous mullite-silicon carbide reinforced blast furnace main ditch castable according to claim 5, characterized in that: In step B1, the flake graphite is 198 flake graphite with a particle size of 80-100 mesh, and the temperature of the vacuum drying oven is 100-110°C.
7. The microporous mullite-silicon carbide reinforced blast furnace main ditch castable according to claim 5, characterized in that: In step B2, the metallic silicon is 98 metallic silicon, the silicon carbide particle size is 2-5 μm, the polymer binder is one of epoxy resin and acrylic resin, the weight ratio of pretreated flake graphite, metallic silicon, silicon carbide powder, and organic polymer binder is 12-14 g: 1-2 g: 1-2 g: 50-60 mL, and the post-processing operation includes: placing the mixed mucus in a muffle furnace, raising the temperature of the muffle furnace to 500-800 ° C, heat preservation for 5-6 hours, cooling and discharging, crushing, and passing through a 200-mesh sieve to obtain a modified flake graphite precursor.
8. The microporous mullite-silicon carbide reinforced blast furnace main ditch castable according to claim 5, characterized in that: In step B3, the modified flake graphite precursor and the surfactant KS1055 are used in a ratio of 10-15 g: 50-60 mL; the post-treatment method includes: after aging, suction filtration, and washing the filter cake with purified water until After neutralization, the filter cake is dried and transferred to a drying oven at a temperature of 80-90°C, vacuum dried to constant weight, crushed, Pass through a 200-mesh sieve to obtain modified graphite.
Citation Information
Patent Citations
Fast-baking explosion proof type refractory castable for blast furnace iron runner
CN102633513A
Ammonium ion stable silica sol combined iron runner castable
CN113354401A
Baking-free iron runner castable for hot jacket repair at iron falling point and use method of baking-free iron runner castable
CN117756508A
Refractories for manufacture iron and steel
KR100708414B1